2015
DOI: 10.1016/j.oraloncology.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and kinetics of cervical lymph node regression after radiation therapy for human papillomavirus-associated oropharyngeal carcinoma: Quantitative image analysis of post-radiotherapy response

Abstract: Background and Purpose We sought to characterize the pattern of lymph node regression and morphology following definitive radiation therapy (RT) for human papilloma virus (HPV)-associated oropharyngeal carcinoma in patients with disease control. Materials and Methods Radiographically positive cervical lymph nodes from patients treated with definitive RT for HPV-associated oropharyngeal carcinoma were segmented on initial pre- and subsequent post-RT contrast enhanced CT images. Pre-specified quantitative noda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…(1,2) Using daily or weekly 3D image guidance, HPV-positive oropharyngeal tumors often demonstrate a complete radiologic response shortly after completing definitive radiation therapy. (3) However, the pre-treatment identification of radiosensitive tumors and host factors associated with radiosensitivity remains a fragmented story for other tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) Using daily or weekly 3D image guidance, HPV-positive oropharyngeal tumors often demonstrate a complete radiologic response shortly after completing definitive radiation therapy. (3) However, the pre-treatment identification of radiosensitive tumors and host factors associated with radiosensitivity remains a fragmented story for other tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…The seemingly weaker informativeness of delta texture features may be due to the (I) inherent artifacts of CBCT scans and metal artifacts from dental implants that could interfere with accurate quantification of texture features and (II) the inherent heterogeneity of both primary and nodal structures in this dataset making broad changes in texture features over time difficult to interpret. Prior retrospective CT studies evaluating the evolution of morphology of nodes following CRT have shown that baseline hypodensity/fat sub-volume component, volume/size, and HU standard deviation were associated with response/regression following therapy (45).…”
Section: Discussionmentioning
confidence: 99%
“…HPV-OPC status is of importance since it has unique histopathological characteristics, distinct epidemiology and improved response to CRT. Differing patterns of lymph node response have been noted in the HPV-OPC population, with a greater initial involution but then a more prolonged and inconsistent reduction in size, particularly in the presence of low-density lymph nodes on CT [24][25][26].…”
Section: Discussionmentioning
confidence: 99%